Uma discussão sobre as práticas de contabilidade de gestão estratégica - Pires, Rui A.R. (2018)
The main purpose of this paper is to provide a discussion on Strategic Management Accounting (SMA) practices in order to obtain a more complete list of SMA practices. We started of prior lists presented for other authors. In addition to external and long-term orientation, and financial and non-financial measurement typologies criteria for SMA practices, we considered an internal resources and capabilities orientation to support external competitive bases. We obtained a list with 22 SMA practices related with: i) costing; ii) planning, control and performance measurement; iii) identification, measurement and management of intellectual capital resources; iv) strategic decision making; v) strategic investment analysis; vi) competitor accounting; and, vii) customer accounting. Therefore, this paper contributes to clarify the concept and purpose of SMA, and the set of SMA practices. In this way, it assists researchers and practitioners in research and adoption of SMA.